Die Gestaltung kooperativer Lernsituationen im inklusiven Mathematikunterricht mithilfe fachdidaktischer Unterstützung: Herausforderungen, Erfahrungen und Sichtweisen von Lehrkräften aus der Grundschule (mathematica didactica, 2022)
The article presents results of a study, in which regular teachers and special education teachers are supported in the implementation of cooperative learning situations in inclusive mathematics classrooms in primary school. According to their own statements, the participating teachers primarily realize teacher-directed and individualized lessons with only few phases of joint learning, in which children learn mathematics cooperatively at different levels. Especially regular teachers seem to need inclusion-related didactical knowledge to implement cooperative learning situations. In addition, it needs to be clarified how the expertise of special education teachers can be incorporated beneficially into teaching.